PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KEDISIPLINAN IBADAH SISWA NURUL AMALIYAH TANJUNG MORAWA - Dyah Utami Hadiprawira; Ramlan Padang; Romad Efendi Sipahutar (Yayasan Haiah Nusratul Islam, 2026)
This study employed a qualitative approach with descriptive methods. Data were obtained through interviews, observation, and documentation. The informants included Islamic Religious Education teachers, homeroom teachers, and seventh-grade students. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. Data validity was validated using source and technique triangulation. The results of the study indicate that Islamic Religious Education teachers play a significant role in shaping students' religious discipline. This role is realized through providing role models, fostering the habit of congregational prayer, fostering morality, guiding religious practices, and providing ongoing motivation and supervision. Strategies used include fostering daily religious practices, integrating religious values ​​into learning, a persuasive and exemplary approach, providing rewards, and enforcing school rules. Supporting factors in fostering discipline include a religious school environment, adequate religious facilities, and support from the principal and other teachers. Inhibiting factors include a lack of motivation among some students, the influence of the external environment, and varying family backgrounds. In conclusion, the role of Islamic Religious Education (PAI) teachers is highly influential in shaping the religious discipline of seventh-grade students at Nurul Amaliyah Junior High School, Tanjung Morawa. This role can be optimally implemented if supported by the school environment, parental cooperation, and a consistent and sustainable coaching approach. This research is expected to contribute to the development of Islamic Religious Education (PAI) learning practices and the development of students' religious character in schools.